Post-polypectomy colorectal bleeding: current strategies and the way forward - Nilanga Nishad; Mo Hameed Thoufeeq (Clinical Endoscopy)
Post-endoscopic mucosal resection (EMR) bleeding, or clinically significant post-EMR bleeding, is influenced by factors such as polyp size, right-sided colonic lesions, laterally spreading tumors, anticoagulant use, and comorbidities like cardiovascular or chronic renal disease. The optimal prophylactic therapy for post-EMR bleeding remains unknown, with no consensus on specific criteria for its application. Moreover, prophylactic measures, including clipping, suturing, and coagulation, have produced mixed results. Selective clipping in high-risk patients is cost-effective, whereas universal clipping is not. Studies and meta-analyses indicate that routine prophylactic clipping does not generally reduce post-polypectomy bleeding but may be beneficial in cases of large proximal lesions. Some studies have revealed that the post-polypectomy bleeding risk after EMR of transverse colonic lesions is lower than that of the ascending colon and caecum, suggesting limited efficacy of clipping in the transverse colon. Cost-effectiveness studies support selective clipping in high-risk groups, and newer static agents such as PuraStat are alternatives; however, their cost-effectiveness is undetermined. Further research is required to establish clear guidelines and refine prophylactic strategies to prevent post-EMR bleeding.